2011
DOI: 10.1590/s0103-21002011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da esperança em pacientes com doença crônica e em familiares ou cuidadores

Abstract: Objectives:To evaluate the level of hope among the three different groups and correlate their levels with demographic and clinical variables. Methods: Descriptive study with a sample of 131 individuals (including 47 cancer patients, 40 diabetic patients and 44 caregivers/ family / caregivers) responding to Hertha's Scale of Hope, Rosenberg's Self-esteem Scale, the Beck Depression Inventory, and an instrument including personal data. Results: There was no difference in hope scores between groups. Hope was posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
1
6
0
10
Order By: Relevance
“…The lack of hope makes it opaque, without goals, waiting for death, which is leaving them vulnerable to the emergence of geriatric and iatrogenic syndromes. Considering the results of the application of Herth's Hope Scale and analyzing the 12 affirmatives that compose it, it was identified that the variable with the lowest mean value obtained was item 03 "I feel very alone", with 2 , 73 of mean, thus indicating that 76.9% of the sample disagreed with the affirmative of number 3, and that it is in agreement with a study with women with HIV (20), who also found this affirmative with the lowest score, contemplating Average of 2.29, realizing that currently individuals with chronic diseases receive support and live surrounded by friends, family and significant people, abstaining from social isolation and preserving interaction and mutual help.…”
Section: Resultssupporting
confidence: 78%
“…The lack of hope makes it opaque, without goals, waiting for death, which is leaving them vulnerable to the emergence of geriatric and iatrogenic syndromes. Considering the results of the application of Herth's Hope Scale and analyzing the 12 affirmatives that compose it, it was identified that the variable with the lowest mean value obtained was item 03 "I feel very alone", with 2 , 73 of mean, thus indicating that 76.9% of the sample disagreed with the affirmative of number 3, and that it is in agreement with a study with women with HIV (20), who also found this affirmative with the lowest score, contemplating Average of 2.29, realizing that currently individuals with chronic diseases receive support and live surrounded by friends, family and significant people, abstaining from social isolation and preserving interaction and mutual help.…”
Section: Resultssupporting
confidence: 78%
“…According to the results of another study in Iran, despite the positive attitude of doctors towards DNR orders, absence of a clear legal guidance regarding this issue leads to various problems in physician's decision-making and necessitates clear instructions/rules from governing bodies in the country (15). Notably, diseases, as one of the factors giving rise to major changes in the lives of people, affect both the patients and their families (16). On the other hand, a study conducted in Iran demonstrated that major clinical challenges, from the view point of medical students, were rooted in not respecting the patient's autonomy (1).…”
Section: Introductionmentioning
confidence: 99%
“…Já a relação com a esperança altruísta foi negativa e fraca. Conforme Balsanelli et al (2011), a ausência de esperança leva o indivíduo a não ter perspectivas futuras, sem motivação e sem objetivos de vida ele vive a espera da morte, um dos sintomas característicos da depressão. Já a presença elevada de esperança auxilia o indivíduo a ter resiliência, tornando-o motivado a enfrentar a patologia em busca de um progresso no estado psicológico (Schuster, Feldens, Iser, & Ghislandi, 2015).…”
Section: Discussionunclassified